Effect of biofeedback training on operator’s cognitive performance - Sutarto, Auditya Puwardini; Abdul Wahab, Muhammad Nubli; Mat Zin, Nora (IOS Press, 2013)
BACKGROUND: Predominantly cognitive tasks assigned to the shop floor can lead to decreased cognitive functions problems,thereby increasing occupational accident risks. A potential approach to prevent such circumstances is by improving operator’s cognitive performance.